Innovative Forward Thinking for Dentists that want to make a Difference - Winston Patrick Kuo (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
The approach in treating patients has shifted to a more personalized approach not only in the medical ecosystem, but becoming more evident in dental medicine. The name of the game in dentistry is "prevention", and most patients that visit the dental office, generally have issues related to their dentition, whether it be caries, a root canal, missing teeth and restorations (which can all be prevented), but a portion, presents with oral diseases that range from periodontal issues to more severe problems, such as oral cancer (also preventable, if detected early). However, the mouth also presents with oral manifestations of a larger systemic problem, including the likes of diabetes, heart and lung complications. The dentist is the second most visited health professional other than your primary care physician, which indicates our role as a healthcare professional should be more engaging to the well-being of an individual as it is related to the person's overall health. Of course, there are obvious limitations in what a dentist can perform on a patient is versus a medical doctor; but a common procedure when visiting our primary care provider is drawing of blood and at times urine, collected for measuring a variety of analytes to indicate whether we are healthy or something requiring further workup. On the other hand, we as dentists do not routinely collect saliva for any purpose, a sample that is non-invasive and easy to collect.